Molecular Profiling of Mammary Analog Secretory Carcinoma Revealed a Subset of Tumors Harboring a Novel ETV6-RET Translocation: Report of 10 Cases - Skalova, Alena; Vanecek, Tomas; Martinek, Petr; Weinreb, Ilan; Stevens, Todd M; Simpson, Roderick H W; Hyrcza, Martin; Rupp, Niels J; Baneckova, Martina; Michal, Michael; Slouka, David; Svoboda, Tomas; et al. (The American journal of surgical pathology, 2018)
ETV6 gene abnormalities are well described in tumor pathology. Many fusion partners of ETV6 have been reported in a variety of epithelial, mesenchymal, and hematological malignancies. In salivary gland tumor pathology, however, the ETV6-NTRK3 translocation is specific for (mammary analog) secretory carcinoma, and has not been documented in any other salivary tumor type. The present study comprised a clinical, histologic, and molecular analysis of 10 cases of secretory carcinoma, with typical morphology and immunoprofile harboring a novel ETV6-RET translocation.
Keywords: Biomarkers, Tumor; Repressor Proteins; Transcriptome; lidé; Middle Aged; Adult; nádorové biomarkery; Gene Expression Profiling; registrace; Proto-Oncogene Proteins c-ets; stanovení celkové genové exprese; protein ETS, translokační varianta 6; In Situ Hybridization, Fluorescence; fenotyp; represorové proteiny; Female; ETS Translocation Variant 6 Protein; fúze genů; sekreční karcinom mamárního typu; Mammary Analogue Secretory Carcinoma; nádory slinných žláz; Phenotype; imunohistochemie; Humans; Predictive Value of Tests; vysoce účinné nukleotidové sekvenování; protoonkogenní proteiny c-ret; High-Throughput Nucleotide Sequencing; Registries; translokace genetická; Immunohistochemistry; lidé středního věku; hybridizace in situ fluorescenční; mužské pohlaví; Translocation, Genetic; genetická predispozice k nemoci; Proto-Oncogene Proteins c-ret; protoonkogenní proteiny c-ets; ženské pohlaví; transkriptom; Salivary Gland Neoplasms; Male; Aged; Genetic Predisposition to Disease; Gene Fusion; dospělí; prediktivní hodnota testů; senioři